EKSISTENSI ADAT ISTIADAT SUKU HUTAN DALAM KEHIDUPAN SEHARI-HARI - Herdianto Surya, Willy (EDUTECH CONSULTANT, 2017)
This paper is the case study have the shape of sociology-anthropology study about existing tradition in to society of forest tribe in the countryside Kembung Luar of Bantan Sub-District of Bengkalis Region. More circumstantial study want to sees, wether tradition will has been run by forest society in intact hereditary or tradition has esperienced of changes or maybe has losted at all. Changes of culture social surely will happens in each ethnic group and that thing happened at forest tribe society in study area. Nevertheless, change causation are more caused by the happening of government changing system, economic advantage and culture social that finally will cause the happening of change in social system, kinship and marriage in tradition of forest tribe society.